Robust Antibody Responses to the BNT162b2 mRNA Vaccine Occur Within a Week After the First Dose in Previously Infected Individuals and After the Second Dose in Uninfected Individuals - Hirotsu, Yosuke; Amemiya, Kenji; Sugiura, Hiroki; Shinohara, Miyuki; Takatori, Mika; Mochizuki, Hitoshi; Omata, Masao (Frontiers in Immunology, 2021)
Background Vaccines against severe acute respiratory syndrome coronavirus 2 can trigger acquired immunity in infection-naïve individuals and offer a path toward ending the coronavirus disease pandemic that began in 2019. However, the kinetics of early antibody responses in vaccinated individuals remain poorly understood. Method We followed BNT162b2 mRNA-vaccinated health care workers (HCWs, N=108) including 103 infection-naïve and five previously infected individuals. A total of 763 blood samples were collected weekly or hourly basis before and after vaccination. Serological analysis of anti-spike and anti-nucleocapsid antibodies was performed. Results Seroconversion occurred in all infection-naïve HCWs 3 weeks after the first dose (just before the second vaccination) and a marked boosting effect was observed at 4 weeks (1 week after the second dose). Among previously infected HCWs with pre-existing antibodies against the spike protein, a remarkable boosting effect was observed during the first week after vaccination, and a further increase in antibody titres was observed after the second dose. In one previously infected patient, daily blood sampling was conducted. Antibody titres began to increase 96 hours (4 days) after the first dose. Conclusion The BNT162b2 mRNA vaccine remarkably enhanced antibody responses after the second dose in infection-naïve individuals and after the first dose in previously infected HCWs of all ages and genders. Antibody titres decreased slightly after the 5th week post-vaccination. The robust boosting effect of immunisation suggests that increased antibody titres following exposure to the virus may restrict viral replication, prolong the incubation period or lessen the severity of disease.